Kinerja Dinas Sosial, Pemberdayaan Perempuan dan Perlindungan Anak Dalam Pemerataan Bantuan Sosial Pangan Kepada Masyarakat di Desa Salamwates Kabupaten Trenggalek - Clareza Arum Anugeraheni; Lukman Arif (Jurnal Kewarganegaraan, 2022)
Abstract The government has an important role in distributing resources and providing services to the community. Local government also participated in this matter. Based on the principle of regional autonomy, the government is given the freedom to regulate and manage government affairs in order to maximize its performance. This study aims to find out and analyze the performance of the Social Service in the distribution of the 2022 Food Social Assistance (BSP) to the community in Salamwates Village, Trenggalek Regency. The type of research used in this study is descriptive with a qualitative approach. The research focus used in this research is productivity, service quality, responsiveness, responsibility, and accountability. Sources of data obtained by researchers in conducting this research are key informants, observations, and documentation. The data analysis method used in this study is the method developed by Miles and Huberman. As well as the validity of the data used, namely the degree of trust (credibility), transferability (transferability), dependability (dependability), and certainty (confirmability). The results of this study found that productivity, service quality, responsiveness, responsibility and accountability had been carried out well even though there were some things that seemed sudden Keywords: BSP, Performance, Distribution Equity,